2015
DOI: 10.1186/s12711-015-0110-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing identifies a homozygous deletion encompassing exons 17 to 23 of the integrin beta 4 gene in a Charolais calf with junctional epidermolysis bullosa

Abstract: BackgroundSince 2010, four Charolais calves with a congenital mechanobullous skin disorder that were born in the same herd from consanguineous matings were reported to us. Clinical and histopathological examination revealed lesions that are compatible with junctional epidermolysis bullosa (JEB).ResultsFifty-four extended regions of homozygosity (>1 Mb) were identified after analysing the whole-genome sequencing (WGS) data from the only case available for DNA sampling at the beginning of the study. Filtering of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…Since with this approach, we investigated only the small variants that were located in coding regions [20], we then searched for structural variations in candidate genes using the Integrative Genomics Viewer (IGV) [21]. The study of EDA , EDAR , EDARADD and WTN10 revealed a 3.8-Mb inversion with breakpoints located in the first intron of EDA and the first intron of XIST (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since with this approach, we investigated only the small variants that were located in coding regions [20], we then searched for structural variations in candidate genes using the Integrative Genomics Viewer (IGV) [21]. The study of EDA , EDAR , EDARADD and WTN10 revealed a 3.8-Mb inversion with breakpoints located in the first intron of EDA and the first intron of XIST (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Si une insertion ou délétion d'un multiple de 3 conduit à la perte ou l'ajout d'acides aminés dans une protéine peu modifiée, une taille non multiple de 3 induit un décalage du cadre de lecture, donc à une séquence d'acides aminés complètement différente et, généralement, un codon stop prématuré. Une délétion de grande taille peut conduire à la perte d'exons, donc de parties de la protéine, comme dans le cas du gène ITBG4 responsable de cas d'épidermolyse bulleuse jonctionnelle en race Charolaise (Michot et al 2015), voire à la protéine complète. Des mutations dans les introns peuvent conduire à des épissages alternatifs, donc à des pertes ou gains d'exons.…”
Section: / Les Types De Mutations De L'adn Conduisant à Des Anomaliesunclassified
“…Capitan et al (2012) ont montré l'impact d'une grande délétion incluant le gène ZEB2 en race charolaise, avec des conséquences sévères sur différentes fonctions. Michot et al (2015) ont montré qu'une délétion de 4,8 kb dans le gène ITGB4 induisait une épidermolyse bulleuse jonctionnelle en race Charolaise. Kadri et al (2014) ont mis en évidence une grande délétion de 660 kb avec un effet très délétère sur la fertilité en race Rouge nordique.…”
Section: / Recherche De Variants Candidatsunclassified